2013
DOI: 10.6035/sapientia76
|View full text |Cite
|
Sign up to set email alerts
|

The musical theatre as a vehicle of learning: an educational innovation project at the university

Abstract: The Musical Theatre as a Vehicle of Learning -UJI -DOI: http://dx.doi.org/10.6035/Sapientia76

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The results confirmed that the CCSES questionnaire is a valid and reliable instrument to measure social competence in higher education and confirmed empirical evidence for the three-factor framework -group climate, team cohesion, and social skills- of the original instrument ( Pérez-Aldeguer, 2013b ). These three variables explained the 67.47% of the variance according to the responses of participants in the study.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The results confirmed that the CCSES questionnaire is a valid and reliable instrument to measure social competence in higher education and confirmed empirical evidence for the three-factor framework -group climate, team cohesion, and social skills- of the original instrument ( Pérez-Aldeguer, 2013b ). These three variables explained the 67.47% of the variance according to the responses of participants in the study.…”
Section: Discussionsupporting
confidence: 78%
“…Since the academic year 2008/2009 Pérez-Aldeguer (2013a , b , 2016 ) has been developing and shaping a project – an Educational Musical Theater – to enhance higher education students’ cooperation and interaction. From the beginning of the process until the final performance, students need to have a continuous face-to-face interaction and cooperation to find a consensus, to solve problems, to achieve a common goal, and to overcome challenges, among others ( Pérez-Aldeguer, 2013b ). After the development of the pilot project it was found that several difficulties arose between the participants.…”
Section: The Development Of the Social Competence In Higher Educationmentioning
confidence: 99%
See 2 more Smart Citations